Kurikulum Anti Radikalisme (Studi Kasus Pada Madrasah Aliyah Negeri Insan Cendikia) - Abdi, Muhammad Iwan; Sayuri, Sayuri; Saparuddin, Muhammad (Lembaga Penelitian dan Pengabdian kepada Masyarakat, UIN Sultan Aji Muhammad Idris Samarinda, 2020)
This research is present to provide an alternative solution for photographing the curriculum development model at Madrasah Aliyah Negeri Islam Cendikia (MAN-IC) in Indonesia. The aims of this research are to photograph the form of the curriculum developed by MAN-IC, examine the MAN-IC curriculum with its various development components, explore and examine the efforts made by MAN-IC in countering radicalism that is rife on social media, and photograph examples of cases that have occurred related to radicalism among students and handling techniques. Data collection techniques in this research include observation, interviews and documentation. Based on the author's findings, a conclusion can be drawn, the study of the anti-radicalism curriculum at MAN IC in Indonesia includes four components, namely the objective component, the material/content component, the method and strategy component and the evaluation component. The goal components in it are developed by the concepts of independence, achievement and religion. Content/material components, apart from MAN IC implementing a boarding school system, efforts to overcome radicalism are also carried out in learning, namely by integrating science with character education values in each learning session. The method and strategy component, namely MAN IC, has made a series of efforts to prevent negative behavior that might be carried out by its students, including creating a series of rules/regulations, designing an IT system that can protect students from using sites that are considered useless, foster parent methods. Which makes teachers as foster parents for students, coaching guidance and counseling teachers for student problems or following up on cases that occur either persuasively or classically. The most effective assessment component in preventing radicalism is continuous and intensive observation regarding students' attitudes (affective).